Characterization of Antimicrobial Edible Films with Single and Double Emulsions from Clove (Syzygium aromaticum) Oil - Kam Natania; Giovani Fransisca Setiawan (Dept. of Chemical Engineering, Diponegoro University, 2020)
Clove oil as a potent antimicrobial agent was added to enhance the properties of edible films. Clove oil was converted to single and double emulsion emulsions for homogenous dispersion in a starch based edible film suspension. Double emulsion was made with two steps emulsification with CaCl2 as inner water phase and guar gum as outer water phase. Single emulsion was prepared similarly without inner water phase. The physico-chemical characteristics and the antimicrobial activity of the of starch-based edible film added with the emulsion were observed. MBC/MFC of clove oil was determined against E. coli, S. aureus, R. stolonifer, and A. niger which gives value of 1.95, 1.46, 0.52, and 0.35 mg/ml respectively. Incorporation of different emulsions on starch-based edible films affect the properties of resulting edible films by increasing thickness, opacity, elongation at break, water vapor transmission rate, and swelling index. Both emulsions showed comparable physicochemical characteristics such as thickness, WVTR, and swelling index value. However, double emulsion produced more superior edible films in terms of tensile strength and antimicrobial activity. 15% addition of double emulsion were able to show strong antimicrobial activity with inhibition zone of more than 8.0 mm for E. coli and 24.0 mm for R. stolonifer.Keywords: clove oil; edible film; single and double emulsion